2000
DOI: 10.1007/bf03033323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imidazenil, a new benzodiazepine receptor partial agonist, in the treatment of convulsions in organophosphate intoxications

Abstract: Anticonvulsant and antilethal effects of imidazenil, a new imidazobenzodiazepine derivative, in fluostigmine (DFP; diisopropyl phosphorofluoridate) intoxications were studied and compared with the effects of diazepam on mice and rats. Special attention was payed to the myorelaxant effects of both drugs. It was stated that imidazenil (i) significantly decreased convulsion intensity in mice, (ii) quickly inhibited seizure patterns in bioelectrical activity in the rat's brain, (iii) significantly increased antile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Like NAs, paraoxon and DFP lead to benzodiazepine‐refractory SE . However, several groups have found that the alternative benzodiazepine imidazenil may offer better and more potent seizure control than diazepam . Thus far, no other studies have been published using OP models to test novel anticonvulsants, but this will change with the recent announcement of the National Institute of Neurological Disorders and Stroke's CounterACT Neurotherapeutics Screening Program .…”
Section: Pesticide Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like NAs, paraoxon and DFP lead to benzodiazepine‐refractory SE . However, several groups have found that the alternative benzodiazepine imidazenil may offer better and more potent seizure control than diazepam . Thus far, no other studies have been published using OP models to test novel anticonvulsants, but this will change with the recent announcement of the National Institute of Neurological Disorders and Stroke's CounterACT Neurotherapeutics Screening Program .…”
Section: Pesticide Modelsmentioning
confidence: 99%
“…65 However, several groups have found that the alternative benzodiazepine imidazenil may offer better and more potent seizure control than diazepam. 66,67 Thus far, no other studies have been published using OP models to test novel anticonvulsants, but this will change with the recent announcement of the National Institute of Neurological Disorders and Stroke's CounterACT Neurotherapeutics Screening Program. 68 A number of anticonvulsant studies have been performed using pilocarpine to induce SE, which has been argued to be a good surrogate for organophosphate exposure.…”
Section: Pesticide Modelsmentioning
confidence: 99%
“…Clearly, controlled studies of the effects of OP anticholinesterases cannot be carried out in humans. Studies of the mechanisms and pharmacology of OPinduced seizures have therefore been performed using animal models, usually mice (75)(76)(77)(78)(79)(80)(81), rats (77,(82)(83)(84)(85) or guinea-pigs (84,(86)(87)(88), but occasionally primates (89-94), and the majority of these have used nerve agents to induce seizure activity.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Thus, IMI elicits a potent anticonvulsant and anxiolytic action at doses that are virtually devoid of sedative and amnesic effects (6,(25)(26)(27)(28)(29)(30)(31). Of note, IMI also potently antagonizes diisopropyl fluorophosphate (DFP)-induced seizures and mortality in rodents (6,32). This drug, at doses up to 60-fold greater than those producing anxiolytic and anticonvulsant actions, antagonizes the sedative and amnesic actions of DZP or alprazolam without causing tolerance (26)(27)(28)(29)(30)33).…”
mentioning
confidence: 99%